(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Candida albicans is an opportunistic pathogen that is commonly found in the human microflora. Virulence activity of pathogens is characterized by biofilm formation, which is characterized by Candida albicans. This study aimed to find the effect of interaction between Candida albicans and some bacteria and their effects on virulent factors of C. albicans such as biofilm formation and hyphal development genes (Sap5 and Ece1). The co-cultivation was performed by mixing each of the bacteria species: Escherichia coli, Staphylococcus aureus, Streptococcus pyogenes, and Pseudomonas aeruginosa with C. albicans for biofilm conditions. The biofilm formation of Candida isolates was detected by the crystal violet assay in a microtitre-plate reader at 620 nm. In this study, Sap5 and Ece1 mRMA expression were indicators for hyphal formation of C. albicans under bacterial action. The optical density (OD620) of C. albicans alone was 0.08, while the OD620 of the biofilm quantification in co-cultured C. albicans mixed with the different bacteria species: P. aeruginosa, E. coli, S. aureus, and S. pyogenes was 0.06, 0.07, 0.09, and 0.27, respectively. The expression level of the Ece1 gene when C. albicans mixed with E. coli and S. pyogenes showed more decreased Ece1 mRNA expression, while the mRNA level of the Sap5 gene was significantly reduced by C. albicans mixed with P. aeruginosa. During the early stages of biofilm development, C. albicans co-cultured with bacteria showed significant differences in biofilm formation and the transcription levels of hyphae-specific genes.